PENGARUH PARTISIPASI PENGANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH MELALUI KOMITMEN ORGANISASI DAN JOB-RELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada SKPD Kabupaten Bengkalis) - Nabilah, Dea Mayang; Ratnawati, Vince; Hariyani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objectives of this study were to prove empirically that organizational commitment job-relevant information might act as an intervening variable affecting the relationship between budgetary participation and managerial performance. Data for this study were collected by using 90 questionnaires, which were distributed to employee with 3rd and 4th grade echelon at 33 Government Offices in Bengkalis District. The sampling method used is purposive sampling. In total 68 questionnaires received were complete and hence usable in analysis. Using path analysis with SmartPLS 3.0 software, the result of this study indicates that the budgetary participation did not effects on managerial performance directly, but has indirectly possitive and significant effects through job relevant information. Meanwhile, budgetary participation positively influence organizational commitment but did not influence managerial performance trough organizational commitment as intervening variable.Keywords: budgetary participation, commitment, job-relevant information, managerial, performance.